1986
DOI: 10.1021/jm00151a010
|View full text |Cite
|
Sign up to set email alerts
|

Potential neuroleptic agents. 4. Chemistry, behavioral pharmacology, and inhibition of [3H]spiperone binding of 3,5-disubstituted N-[(1-ethyl-2-pyrrolidinyl)methyl]-6-methoxysalicylamides

Abstract: A series of 3,5-disubstituted N-[(1-ethyl-2-pyrrolidinyl) methyl]-6-methoxysalicylamides was synthesized, starting from the 2,6-dimethoxybenzoic acids, by boron tribromide demethylation of the corresponding 3,5-disubstituted 2,6-dimethoxybenzamides and separation of the two positional isomers. The correct structure assignments were based on selective decoupling studies on their 13C NMR spectra. The salicylamide derivatives were tested for antidopamine activity in vivo by their ability to inhibit the apomorphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 2 publications
2
32
0
Order By: Relevance
“…That antidepressants reverse CMS-induced anhedonia via the potentiation of DA transmission is indicated by experi-527 ments in which DA receptor antagonists were able to reverse the recovery in sucrose intake in animals successfully treated with both tricyclic and atypical antidepressants (Muscat et al 1990Sampson et al 1991). In the present study, raclopride, a specific D 2 antagonist (De Paulis et al 1986), reversed the antidepressant effects of (_+)-mianserin, and (+)-mianserin. The effect of raclopride was short lasting: recovery of sucrose drinking was again evident on the following, raclopride free test.…”
Section: Discussionsupporting
confidence: 56%
“…That antidepressants reverse CMS-induced anhedonia via the potentiation of DA transmission is indicated by experi-527 ments in which DA receptor antagonists were able to reverse the recovery in sucrose intake in animals successfully treated with both tricyclic and atypical antidepressants (Muscat et al 1990Sampson et al 1991). In the present study, raclopride, a specific D 2 antagonist (De Paulis et al 1986), reversed the antidepressant effects of (_+)-mianserin, and (+)-mianserin. The effect of raclopride was short lasting: recovery of sucrose drinking was again evident on the following, raclopride free test.…”
Section: Discussionsupporting
confidence: 56%
“…We have previously reported that DA antagonists, administered acutely, reversed the therapeutic effects of tricyclic antidepressants within the chronic mild stress paradigm (Muscat et al 1990;Sampson et al 1991). In the present study, raclopride, a specific D2 antagonist (De Paulis et al 1986), selectively reversed the therapeutic effect of fluoxetine and maprotiline: at the low dose used, raclopride had no effect on sucrose consumption in any of the four nonstressed control groups, or in the non-recovered vehicle-or chlordiazepoxide-treated stressed groups, but profoundly decreased sucrose intake in the two antidepressant-treated stressed groups. The effect of raclopride was short lasting: recovery of sucrose drinking was again apparent on the following, raclopride-free test.…”
Section: Discussionsupporting
confidence: 48%
“…These data argue strongly that an increase in DA receptor responsiveness may be responsible for the therapeutic action of tricyclic antidepressants in this model (Muscat et al 1990;Sampson et al 1991). We have therefore investigated the role of dopaminergic mechanisms in the actions of fluoxetine and maprotiline, using an acute challenge with a highly selective D2 receptor antagonist, raclopride (de Paulis et al 1986),…”
mentioning
confidence: 99%
“…Importantly, an interesting in vivo finding was that while apomorphine induced both stereotypy and hyperactivity in the rat, both behaviors are thought to be DA mediated [41–43], H AI is thought to occur through activation of mesolimbic dopaminergic pathways, and S AI through stimulation of nigrostriatal dopaminergic pathways [43,44]; and the ability of DA D2‐like receptor antagonists to inhibit these behaviors can often be described in terms of separation of potency. As stated above, eticlopride was nine times more potent than haloperidol at inhibiting H AI ; however, eticlopride and haloperidol were nearly equipotent at inhibiting S AI , and haloperidol was equipotent in both assays [31,33]. This same phenomenon of separation between inhibition potencies was true for the earlier generation benzamides [45,46] as well as for the more potent 3‐alkyl‐substituted salicylamides [21]; each inhibited H AI at lower doses than required to inhibit S AI .…”
Section: Developmentmentioning
confidence: 88%